2022
DOI: 10.30541/v49i3pp.193-212
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Youth Employment in Pakistan: Are They Youth-Specific?

Abstract: This paper analyses the patterns of and the challenges for youth employment in Pakistan, and examines whether these challenges are youth-specific. Using the 2005-2006 Labour Force Survey (LFS), the analysis includes determinants of unemployment, determinants of working in the formal sector, rate of return on education, and determinants of working hours. The paper finds that many of the challenges to youth employment in Pakistan are not youth-specific. Policies should thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is important to ask whether there is a link between employment and educational levels attained. Hou (2010) finds that the unemployment rate is much higher for better-educated youth. Hou's findings are supported by data in the Labor Force Survey 2014-15, which presents a clear pattern of rising unemployment with increasing education levels for both young males and females (Figure 2.4).…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to ask whether there is a link between employment and educational levels attained. Hou (2010) finds that the unemployment rate is much higher for better-educated youth. Hou's findings are supported by data in the Labor Force Survey 2014-15, which presents a clear pattern of rising unemployment with increasing education levels for both young males and females (Figure 2.4).…”
Section: Employmentmentioning
confidence: 99%
“…While many problems in this sphere apply to adults as well, some challenges are youth-specific, such as the insufficient returns at initial job entry for better-educated youth. For these challenges, more youth-specific interventions are needed (Hou, 2010).…”
Section: The Future Is Nowmentioning
confidence: 99%
“…Arif (2012) estimated the relationship between labor reallocation and sectoral productivity in Pakistan and illustrated that economic growth depends on sectoral structure, in addition, the manufacturing sector absorbs more labor force than the workers move from the agricultural sector to the service sector. Hou (2010) examined the pattern and challenge of youth employment in Pakistan and analyzed that the youth unemployment rate is higher, the labor market had not smooth and most of the young person working without paid as family workers. Nasir (2000) examined the earning differential between the private and public sectors that are divided into two categories formal and informal and concluded that earnings of public sectors had more than the private sector due to their personal human capital qualities.…”
Section: Literature Reviewmentioning
confidence: 99%